Nutritive value of shrimp waste-meal and fly larva-meal (maggot-meal) in growing albino rats - ODUGUWA, O O; FANIMO, A O; ONIFADE, A A; ARIJE, A (The Indian Journal of Animal Sciences, 2013)
Growing albino rats of the Winster strain were used to determine the nutritive value of shrimp waste-meal(SWM) and maggot-meal (MM). Rats (24) were allocated to 4 equal groups of 6 rats each and fed ad lib. 4 different experimental diets. The first was the protein-free basal diet. The other 3 diets contained whole hen’s egg (reference), shrimp waste-meal or maggot-meal as the only protein sources respectively. They supplied 100g/kg protein in the diets. Experiment lasted 21 days. Performance of rats on the MM protein was significantly higher than those fed SWM protein. There were no significant differences (P>0.05) in the relative weightsof lungs, kidneys, spleen and caecum. Rats on SWM, however, had lowest (P<0.05) values of heart, liver and intestine. The packed-cell volume (PCV) did not vary significantly with the dietary treatments, however, the haemoglobin of rats that received MM diet were higher than those on SWM diets. It was concluded that both SWM and MM has potential as protein concentrates but the feeding value of SWM for monogastrics is limited.